2017
DOI: 10.1152/japplphysiol.00970.2016
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual microcirculatory blood flow and vessel density in Sherpas at high altitude

Abstract: Anecdotal reports suggest that Sherpa highlanders demonstrate extraordinary tolerance to hypoxia at high altitude, despite exhibiting lower arterial oxygen content than acclimatized lowlanders. This study tested the hypothesis that Sherpas exposed to hypobaric hypoxia on ascent to 5,300 m develop increased microcirculatory blood flow as a means of maintaining tissue oxygen delivery. Incident dark-field imaging was used to obtain images of the sublingual microcirculation from 64 Sherpas and 69 lowlanders. Seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…, ; Gilbert‐Kawai et al . ). However, it is unknown whether this increase TVD passively follows changes in cardiac output and arterial blood pressure, or whether it is the result of adaptive response of the microcirculation itself.…”
Section: Introductionmentioning
confidence: 97%
“…, ; Gilbert‐Kawai et al . ). However, it is unknown whether this increase TVD passively follows changes in cardiac output and arterial blood pressure, or whether it is the result of adaptive response of the microcirculation itself.…”
Section: Introductionmentioning
confidence: 97%
“…Anatomically, the microcirculation consists of a network of blood vessels whose primary role is regulation of convective blood flow to match micro-regional oxygen demand (Levick, 2009). In a recent study using incident darkfield imaging, Sherpa highlanders demonstrated significantly greater sublingual microcirculatory blood flow and capillary density when compared with lowlanders at high altitude (Gilbert-Kawai et al, 2017). The authors postulated that this increase could provide both a greater flow per unit tissue volume and a greater flow per unit time, both of which would enhance oxygen delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to lowlanders, Sherpa highlanders exhibit a significantly higher number of capillaries per square millimeter of muscle cross-section, which would support efficient and effective diffusion of oxygen to muscles [9]. Moreover, a recent study demonstrated that Sherpas exhibit significantly higher sublingual small vessel density, capillary density, and microcirculatory flow per unit time and per unit volume of tissue compared to lowlanders at 5300 m [10]. These findings suggest the notion that peripheral vascular factors at the microcirculatory level play an important role in the process of adaptation to hypoxia in Sherpa highlanders.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-stimulated physiological vasculogenesis and angiogenesis may increase microcirculatory blood flow and capillary density, thus restoring the oxygen supply in tissues to compensate for oxygen insufficiency [8]. Compared to non-Sherpa lowlanders, Sherpa highlanders show significantly greater capillary density in muscle cross-section [9], and higher sublingual microcirculatory blood flow and greater capillary density at high altitude [10]. These findings indicate efficient and effective oxygen transport to tissues in Sherpa highlanders, supporting the notion that microcirculation plays a critical role in the mechanism underlying adaptation to hypoxia [11].…”
Section: Introductionmentioning
confidence: 99%